النسخة المحدثة لنظام الإدارة البيئية الايزو2015:14001 بين التعديلات العراقيلت العراقيل والمكاسب التي توتاجه المنظمات الأعمال - Mimoune, Mouad; Benchikhe, Siham (Finance and Business Economies Review, 2018)
Today's organizations are facing environmental pressures, and that requires them to turn into the environmental initiatives, and this trend are essential for the organization’s survival in the market. The aim of this article is to provide an analysis of the latest version of the environmental management system (ISO 14001: 2015) which were unveiled in (2015) , its changes to comply with recent international and domestic developments, as well as to reveal its application’s main gains and profits.